Obtaining Oviparous Grass Snake Natrix natrix (Serpentes, Colubridae), embryos at Early Developmental Stages by Caesarean Section - Sheverdyukova, H.; Merzlikin, I. R. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
There is a specific feature in the developmental biology of oviparous snakes:  embryos in the eggs, which were just laid, have already undergone significant development. This fact makes it significantly complicated to obtain data on organs’ development at early stages of embryogenesis. In addition, the fertilization time and the duration of snake pregnancy in the wild are unknown. In order to obtain the embryos of oviparous grass snake Natrix natrix (Serpentes, Colubridae) at successive developmental stages with minimal harm to gravid females we used caesarean section. The past known experience of performing caesarean section in snakes and anesthesia in reptiles were used. All the embryos were taken from the upper oviduct of a female at one time; in this way we eliminated the influence of medications on embryos’ development. The described method is valuable when it is necessary to obtain snake embryos and to preserve the life of the female and, possibly, its reproductive ability.